Safeguarding, Chaplaincy and English Professional Football - Oliver, Mark (Religions, 2019)
In recent years, English professional football has been rocked by allegations of historical sexual abuse and safeguarding concerns around young players. This paper examines the potential contribution that sports chaplains can make to the specific welfare needs of elite youth footballers within the wider context of safeguarding practices and protocols. Comprising a small-scale, sociological study involving welfare personnel at English Premier League and English Football League Championship clubs, the paper identifies the scope and potential of sports chaplaincy in relation to the practical outworking of safeguarding policy. Findings reveal that elite youth footballers face a number of pressures specific to the highly competitive environment in which they work and that various safeguarding issues routinely arise amidst these pressures. The paper concludes by suggesting that sports chaplains are ideally placed to provide safeguarding and wider welfare support to young players as a consequence of their independence from team management structures and their prioritization of holistic care above performance-related issues.